Konstruksi dan Desain Kurikulum Berbasis Pendekatan Experiential Learning John Dewey dalam Konteks Pendidikan Islam di Sekolah dan Perguruan Tinggi - Mutmainah, Rofikasari; Supriyatno, Triyo; Susilawati, Samsul (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2025)
This article examines the application of John Dewey’s experiential learning approach within Islamic Religious Education (PAI), highlighting its relevance in linking theory to practice for a deeper and contextual understanding of religion. Employing a library research method, the study investigates how experiential learning can be integrated into PAI and its implications for cultivating reflective and ethical awareness among students in both schools and higher education. The findings reveal that experiential learning not only enables students to grasp Islamic teachings theoretically but also to internalize their values through reflective practice. Furthermore, it fosters critical thinking and ethical awareness by engaging learners in problem-based learning, case studies, and social participation. The approach also contributes to reconstructing a dynamic Islamic epistemology that connects empirical experience with critical reflection, thereby making Islamic teachings more applicable to everyday life. Overall, experiential learning should be understood not merely as a methodological innovation in PAI but as a transformative strategy for Islamic education to adapt effectively to the challenges of globalization and modernity.‎